Implementation of the Cognitive Approach in the Analysis of Singular-Plural Forms in Arabic Vocabulary Learning - Agil, Idrus Muchsin Bin; Taubah, Miftachul (UIN Mahmud Yunus Batusangkar, Indonesia, 2025)
Arabic is an important international language that is not easy to learn, both for native speakers and foreign learners. In Indonesia, the teaching of Arabic often depends on the teacher’s ability and motivation, which vary widely. This study examines the cognitive approach in teaching Arabic vocabulary (mufradat) at UIN Maliki Malang, which is currently facing low vocabulary mastery among second-semester students. This qualitative research involves observation, interviews, and document analysis, focusing on the role of lecturers as facilitators and the use of cognitive approaches in vocabulary learning. The results of the study indicate that the cognitive approach, which involves mental processes and active student interaction, can enhance students’ understanding and engagement in learning Arabic. The analysis of singular and plural forms in noun sentences helps students develop critical and creative thinking skills, as well as improve learning motivation and self-confidence.